Setting the Right Expectations - Fonseca, João (2023)
Fonseca, J., Bell, A., Abrate, C., Bonchi, F., & Stoyanovich, J. (2023). Setting the Right Expectations: Algorithmic Recourse Over Time. In Proceedings of 2023 ACM Conference on Equity and Access in Algorithms, Mechanisms, and Optimization (EAAMO ’23) [29] ACM - Association for Computing Machinery. https://doi.org/10.48550/arXiv.2309.06969, https://doi.org/10.1145/3617694.3623251---This research was supported in part by NSF Awards No. 1916505 and 192265, by the NSF Graduate Research Fellowship under Award No. DGE-2234660, by research grants from the Portuguese Foundation for Science and Technology (“Fundação para a Ciência e a Tecnologia”) references SFRH/BD/151473/2021 and UIDB/04152/2020, and by the New York University Center for Responsible AI.